Identification, characterization and assessment of bacillus amyloliquefaciens as putative probiont for juveniles blue swimming crab [Portunus pelagicus, (Linnaeus 1758)] to control vibrio harveyi infection - Abdul Rahman, Noor Azrin (2018)
The blue swimming crab, Portunus pelagicus also known as flower crab which is one of the important marine crustacean in Malaysia. However, many blue crab mortalities were attributed by systemic bacterial infections, especially at larval and juvenile stages. The genus Vibrio mainly Vibrio harveyi was commonly found in blue crab. To cater this problem, the present study focused on development of local bacteria as potential probiont in controlling the growth of pathogenic V. harveyi. Eleven potential bacteria were successfully isolated from the hemolymph of four healthy blue swimming crab (P. pelagicus). All isolates were identified as Bacillus amyloliquefaciens by series of biochemical test using triple sugar ion test, oxidase and catalase test, followed by Internal Transcribe Spacer (ITS) gene sequence analysis. The isolates were able to inhibit the growth of V. harveyi in in vitro screening assay by using spot lawn, disc diffusion and well diffusion assay with strong antagonistic activity ranging from 7 to 16 mm. The potential probiont at 108 CFU mL-1 showed highest inhibition response towards V. harveyi after being co-cultured for 48h. The probionts produced three major extracellular enzymes, which were amylase, gelatinase and lipase. The potential probionts were also able to form biofilm after 24h of culture. In in vivo study, B. amyloliquefaciens L9 and B. amyloliquefaciens L11 were used as potential probionts in preliminary study using Artemia as a host. The survival rate of Artemia treated with probionts at concentration of 106 CFU ml-1 showed significant highest survival for B. amyloliquefaciens L9 and for B. amyloliquefaciens L11 (69 ± 0.3% and 62 ± 1.4 % respectively) after challenged with V. harveyi. The results of vibrios count showed that both of probionts were able to reduce the numbers of Vibrio in Artemia at the end of the challenge assay. For axenic hatched, the results showed that the number of probiotic in Artemia increased over time for B. amyloliquefaciens L9 and B. amyloliquefaciens L11. Bacillus amyloliquefaciens L11 at 108 CFU mL-1 took as early as 6h to penetrate into the Artemia meanwhile B. amyloliquefaciens L9 needed longer time to be partially penetrated into the Artemia (12h of incubation) with the same concentration. In in vivo challenged assay using blue crab juveniles, B. amyloliquefaciens L11 was used due to its ability in inhibited V. harveyi during antagonistic activity. Immersion method was implemented using 20 crab juveniles per tanks. The treatment tanks were incubated with probiont for 24h and pathogenic V. harveyi was added on the next day. Results demonstrated that B. amyloliquefaciens L11 had significant highest survival rate 42 ± 0.5 % if compared with V. harveyi only (12 ± 0.8 %) at concentration of 106 CFU mL-1 after 5 days of challenged test. In addition, the results also showed that B. amyloliquefaciens L11 were able to reduced vibrio load, gave slightly increased in crab juvenile weight and length. Gene contents analysis study demonstrated that B. amyloliquefaciens L11 underwent a mutation at different base length and location. Insertion and deletion were the most abundant mutation detected from gene analysis. A 21 bases mutation as deletion occurred at two different gene loci and the longest bases insertion was 39 bases occurred at one gene loci. A number of 73 genes occurred a mutation that cause a structural variation in B. amyloliquefaciens L11 probiotic genome at different location of the sequences. Majority of mutation occurred in non-coding regions and intergenic regions. Antibacterial gene consist within the B. amyloliquefaciens L11 probiont are considered as main factors in antagonistic activity. Lipopeptid and polyketid genes are related in present of antibacterial agents. Overall, based on results of in vitro and in vivo assay, B. amyloliquefaciens could be considered as a promising potential probiotic with antibacterial properties.